Analysis on Tuberculosis in Bintulu from 2013 to 2017 / Mohd izwan Masngut ... [et al.] - Masngut, Mohd izwan; Jaya, Vanessa Julan; Muga, Rona Ruran; Shafie, Farah Ayuni; Md Rashid, Razi Ikhwan (Faculty of Health Sciences, Universiti Teknologi MARA, 2019)
In Malaysia, Tuberculosis (TB) cases has been identified as one of re-emerging communicable disease with high number of death rate. This study aims to analyze the TB incidence trend in Bintulu, Sarawak from 2013 to 2017 using spatial and temporal approach. TB cases were classified by risk factors of gender, age, nationality, occupation, level of education and health status. The XY-coordinates of all 1175 identified cases data were used to generate spatial-temporal maps using ArcMap 10.5 and later for the identification of the hotspots area. Results showed that Bintulu town is the hotspot of TB, with the greatest proportion was among male patients (70.3%), age of 15 to 65 and above, Malaysians (85%), those with no education (29.4%), unemployed patients (26.8%), non-diabetics (85.3%), non-smokers (60.7%) and HIV-negative patients (94.8%). For effective prevention and control, thorough TB screening should be implemented for all citizens and non-citizens in Bintulu. This study also suggest the application of spatial and temporal analysis on TB should be extend for other areas in Sarawak.